Examining the influence of season phase, age, and anthropometrics on body composition trends in National Basketball Association athletes - Russell, J. L.; Baker, B. S.; Mercer, R. A. J.; McLean, B. D. (The Journal of Strength and Conditioning Research, 2025)
This study aimed to describe seasonal body composition changes in NBA athletes using Dual-energy X-ray Absorptiometry (DXA) and to explore the relationship between these changes and factors such as age and anthropometrics. A retrospective analysis was conducted using 402 DXA scans from 62 professional male basketball players, obtained from one NBA team between 2012 and 2023. Seasonal phases were defined as preseason, pre all-star, post all-star, and offseason. A custom region of interest (ROI) method was used to ensure consistent scan areas for taller athletes who exceeded the DXA bed length. Linear mixed models analyzed the influence of seasonal phases, age, and height on lean mass (LM), fat mass (FM), and bone mineral content (BMC). In-season phases (pre all-star and post all-star) showed small increases in LM and decreases in FM compared with the preseason, with no significant BMC changes. Chronological age was associated with increases in LM but not FM. Taller athletes exhibited increases in LM, FM, and BMC. Significant random variance across players and seasons indicated that additional unmeasured factors might influence body composition. NBA athletes generally gain LM and lose FM during the season, with older players showing increased LM gain. The study's novel ROI method provide reliable data for athletes exceeding standard DXA limits, highlighting the importance of tailored body composition assessments in professional basketball. These findings can inform strength and conditioning, nutrition, and player development strategies across different seasonal phases and ages.